Aplicação da escala de desenvolvimento motor de Rosa Neto em crianças com Transtorno do Espectro Autista: um estudo exploratório - Gusman, Silvia (2017)
Introduction and Objectives: Evidence is added that motor development disorders impact the social functioning of individuals with Autism Spectrum Disorder. Systematic studies on the subject are scarce. The aimed of this cross-sectional exploratory-descriptive study with convenience sample were (1) to apply the Rosa Neto Motor Development Scale - EDM in children diagnosed with Autism Spectrum Disorder (ASD); (2) Evaluate fine motor, global motor, balance, body scheme, spatial and temporal organization and laterality in each child of the sample; (3) To test the applicability of the scale comparing the application among children with ASD and children with typical development; (4) Test the hypothesis of applicability of the Motor Development Scale by investigating the reliability between two evaluators. Method: The sample consisted of 10 children with typical development and 10 children diagnosed with ASD, between 6 and 8 years old, male and children with verbal ASD, without intellectual disability and without comorbidities. The evaluation of each child was performed in two moments with interval of at least 1 week, and applied by 2 evaluators. Results: It was possible to identify that children with typical development of the sample are within the normative average of the normal motor development index, and the correlation between the results of the motor areas by 2 evaluators was high, between 0.7 and 0.9 for all measures, except for balance that was of intermediate value, 0.51. Children with ASD are below the normative average motor development index for Brazilian children. There was no difference between the 2 evaluators for all motor profile measurements. The correlations between both were positive. The values were: fine motor: (0,24); global motor: (0,22); balance: (0,40); body scheme / speed: (0,72); spatial organization: (0,63); language / temporal organization: (0,43). Conclusion: The Rosa Neto Motor Development Scale can be applied by different professionals, in different contexts, both in typical children and in children with Autistic Spectrum Disorder, once the applicator training is done.